Paul and the stories of Israel: grand thematic narratives in Galatians - Das, A. Andrew (Fortress Press, 2016)
An introduction to the grand thematic narrative -- The gentile influx into Zion -- Rethinking the covenantal Paul -- The obedient Abraham and Isaac in the Aqedah -- Exodus allusions in Galatians 4:1-7 -- The spirit as exodus cloud -- A narrative of the imperial cult in Asia Minor -- Lessons learned and the path forward